Genome-wide association mapping for resistance against Septoria nodorum blotch and tan spot in a diverse wheat panel - Dehua Wang; Xinyao He; Zhiying Deng; Reynolds, Matthew P.; Dreisigacker, Susanne; Pawan Kumar Singh (Springer, 2025)
Septoria nodorum blotch (SNB) and tan spot (TS) are two globally significant foliar diseases affecting wheat, causing substantial reductions in both yield and grain quality. In this study, genome-wide association study (GWAS) was conducted using an elite diversity panel comprising 150 lines to identify genetic loci associated with resistance to SNB and TS. Resistance was evaluated in greenhouse experiments at the seedling stage, with two replicates for each disease. For SNB, the majority of lines demonstrated good level of resistance, with 53% rated as resistant or moderately resistant (R/MR). Similarly, for TS, 60% of the lines exhibited R/MR resistance. Some lines exhibited high resistance to both SNB and TS. The panel was genotyped with the Illumina Infinium 25 K BeadChip. GWAS revealed several significant marker-trait associations on chromosome 5B associated with SNB resistance, all of which were located in the vicinity of the Tsn1 gene, suggesting its important role in conferring SNB susceptibility within this population. In addition, two quantitative trait loci (QTL) on chromosomes 2AL and 7AS were identified. For TS, significant markers were primarily found within a 20 Mb region on the long arm of chromosome 7B, with phenotypic variation explained ranging from 8.34% to 12.31%. Additional TS QTL with minor effects were identified on chromosomes 3A, 5A, 7A, and 7D. These resistant lines and identification of markers for SNB and TS resistance hold potential for use in wheat breeding programs aimed at improving resistance to the two diseases.